Shadow kiss : a graphic novel - Mead, Richelle (Mead, Richelle. Vampire Academy novel., 2013)
Retold in graphic novel format, while Rose is coping with the darker effects of being shadow-kissed, her relationship with Dimitri is finally taking off, and when he disappears during a Strigoi attack on St. Vladimir's Academy, she must make a terrible choice.